2017
DOI: 10.1007/s11663-017-0974-0
|View full text |Cite
|
Sign up to set email alerts
|

Hot Ductility and Compression Deformation Behavior of TRIP980 at Elevated Temperatures

Abstract: The hot ductility tests of a kind of 980 MPa class Fe-0.31C (wt pct) TRIP steel (TRIP980) with the addition of Ti/V/Nb were conducted on a Gleeble-3500 thermomechanical simulator in the temperatures ranging from 873 K to 1573 K (600°C to 1300°C) at a constant strain rate of 0.001 s À1 . It is found that the hot ductility trough ranges from 873 K to 1123 K (600°C to 850°C). The recommended straightening temperatures are from 1173 K to 1523 K (900°C to 1250°C). The isothermal hot compression deformation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 40 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3][4] In particular, as fully austenitic high-Mn steels with 12-30 wt% Mn, transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) steels have attracted intense attention due to their remarkable mechanical properties, including high strength, excellent ductility, and high energy absorption capacity, and are promising candidate for the fourth-generation automotive steels. [5][6][7] Therefore, most studies of high-Mn steels have focused on their mechanical properties such as solidification structures, [8,9] nonmetallic inclusions, [10][11][12] tensile ductility [13,14] and deformation behavior, [15,16] etc., whereas studies of the smelting process have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, as fully austenitic high-Mn steels with 12-30 wt% Mn, transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) steels have attracted intense attention due to their remarkable mechanical properties, including high strength, excellent ductility, and high energy absorption capacity, and are promising candidate for the fourth-generation automotive steels. [5][6][7] Therefore, most studies of high-Mn steels have focused on their mechanical properties such as solidification structures, [8,9] nonmetallic inclusions, [10][11][12] tensile ductility [13,14] and deformation behavior, [15,16] etc., whereas studies of the smelting process have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on the formation, removal, and modification of non-metallic inclusions in the molten steel at steelmaking temperatures have been conducted, such as the calcium treatment [7][8][9][10][11][12][13][14][15], the rare earth element treatment [16,17], slag refining [18][19][20][21][22], and reoxidation [23,24]. However, less attention has been paid to the variation of oxide inclusions in the solid steel during heat treatment.…”
Section: Introductionmentioning
confidence: 99%